THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE DIGITALIZATION AND AUTOMATION OF BIOCHEMICAL ANALYSIS (Modern American Journal of Medical and Health Sciences, 2025)
The rapid advancement of digital technologies and artificial intelligence (AI) has significantly transformed the field of biochemical analysis. By integrating AI algorithms with automated laboratory systems, medical diagnostics have become faster, more accurate, and more reliable. Digitalization enables the efficient collection, processing, and storage of biochemical data, while automation minimizes human error and enhances workflow efficiency. Artificial intelligence plays a crucial role in interpreting large volumes of biochemical information, identifying hidden patterns, and supporting clinical decision-making. This paper discusses the impact of AI on the digitalization and automation of biochemical analysis, focusing on its practical applications, technological innovations, and the future potential of intelligent laboratory systems.